2019
DOI: 10.1002/ijfe.1747
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic news, public communications, and foreign exchange jumps around U.S. and European financial crises

Abstract: Jumps in the Euro, Pound, and Yen, based on 5‐minute returns for the period 2004–2015, are shown to be state dependent between recessions and expansions in their response to macroeconomic news announcements and speeches by treasury and central bank senior officials. We find evidence of large jumps and cojumps response to the Federal Open Market Committee rate decision consistently over economic states. U.S. news is more important than EU news and jump magnitude and probability exhibit positive responses. Feder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…These levels of abnormal variation are mainly the result of speeches by senior European officials. Ayadi et al (2020) reported that scheduled news announcements and speeches have a significant effect on jumps, but scheduled news is more influential than speeches because it is announced more frequently. They also showed that speeches by the Fed, the ECB and the Bank of England officials significantly impact price increases.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…These levels of abnormal variation are mainly the result of speeches by senior European officials. Ayadi et al (2020) reported that scheduled news announcements and speeches have a significant effect on jumps, but scheduled news is more influential than speeches because it is announced more frequently. They also showed that speeches by the Fed, the ECB and the Bank of England officials significantly impact price increases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…2. Please see Ayadi et al (2020, 2022), Dewachter et al (2014), Blinder et al (2008), Fratzscher (2006) and Ehrmann and Fratzscher (2007).…”
Section: Notesmentioning
confidence: 99%
“…Price movements in financial assets are originated in an event-based approach, such as news or announcement of political-economic origin. The events influence in economic agent decisions to maintain national or foreign assets (Andersen, Bollerslev, & Dievold, 2007;Ayadi, Omrane, Wang, & Welch, 2019). Factors such as inflation and interest rate differentials between countries generate volatility in the exchange rate (Jeelani, Tomar, Das, & Das, 2019).…”
Section: Introductionmentioning
confidence: 99%